China and south asia : changing regional dynamics, development and power play - Ranjan, Rajiv; Guo, Changgang (London : Routledge India, 2021)
This book looks at the changing dynamics and regional power play between China and South Asia. It explores crucial issues such as China-Pakistan Economic Corridor and the changing nature of China-India relations; China's trident approach in South Asia and its rising influence in the region;theresponses of small states to rising China; China's twenty-first-century Belt and Road Initiative; China and India; China's rise and the USA's security policy vis--vis India; the Shanghai Cooperation Organization and regional security; and Russia's Pivot to the East' and its impact on the Asia-Pacific region. The volume brings together theviews of scholars from China, South Asia and beyond on different aspects of China and South Asia engagement, including regional politics, connectivity, infrastructure and development projects, power politics, economy, ideology and culture. The chapters offer insights into trends and challenges within China's economic and security environment as impacted by globalization, regional interests and the demands of cooperation. They present critical, comprehensive and expert analyses of China's engagement with South Asia by covering historical, sociological, political, cultural, economic and strategic factors while including perspectives from individual countries. This volume will be useful to scholars and researchers of Chinese studies, politics and international relations, South Asian studies, foreign policy, diplomacy, security and strategic studies and political studies, as well as to those in media, policymakers, bureaucrats, diplomats and think tanks.
Included indexes (pages 268-277)
Keywords: China -- Foreign relations -- South Asia; South Asia -- Foreign relations -- China; China -- Foreign economic relations -- South Asia; South Asia -- Foreign economic relations -- China; POLITICAL SCIENCE / General; SOCIAL SCIENCE / General